Current viewpoints on platelet contribution to inflammation - Etulain, Julia (2012)
Inflammation is an underlying feature of a variety of human diseases. Because inflammatory diseases are a major cause of morbidity and mortality in developed countries, understanding the interaction of the most important factors involved is an important challenge. Although platelets are widely recognized as having a critical role in primary hemostasis and thrombosis, basic and clinical evidence increasingly identifies these enucleated cells as relevant modulators, as both effector and target cells, of the inflammatory response. The cross-talk between platelets, endothelial cells and leukocytes in the inflammatory milieu mat be seen as a double-edged sword which functions not only as an effective first-line defense mechanism but may also lead to organ failure and death in the absence of counter-regulation systems. The molecular mechanisms involved in the reciprocal activation of platelets, endothelial cells and leukocytes are beginning to be elucidated. In the light of the existing data from experimental and clinical studies it is conceivable that platelet adhesion molecules and platelet mediators provide promising targets for novel therapeutic strategies in inflammatory diseases. The potentially adverse effects of these approaches need to be carefully addressed and monitored, including alterations in hemostasis and coagulation and particularly the impairment of host defense mechanisms, given the recently identified pivotal role of platelets in pathogen recognition and bacterial trapping. In this review we discuss the most important recent advances in research into the cross-talk between platelets and vascular cells during inflammation and the clinical consequences of these interactions.